Impact of polystyrene microplastics with combined contamination of norfloxacin and sulfadiazine on Chrysanthemum coronarium L. (1st January 2023) - Khan, Kiran Yasmin; Li, Guanlin; Du, Daolin; Ali, Barkat; Zhang, Shuang; Zhong, Meiying; Stoffella, Peter Joseph; Iqbal, Babar; Cui, Xiaoqiang; Fu, Lijiang; Guo, Ya
Abstract: Antibiotics and microplastics including nanoplastics are emerging contaminants which have become global environmental issues. The application of antibiotics along with microplastics in soil and their entrance in food chain may pose a major threat to human health. The single and combined exposure of polystyrene microplastic (MPS), norfloxacin (NF) and sulfadiazine (SFD) on Chrysanthemum coronarium L . a medicinal food crop, were investigated. Accumulation of nutrient element contents (Fe, Mn, Mg, Zn, K) differentially responded to the single or combined treatments compared to the control. Scanning electron microscopy and transmission electron microscopy analysis indicated that MPS, NF and SFD accumulated in roots, shoots, and leaves and affected their ultrastructure. Compared with that of the single contamination, the co-contamination of microplastics and antibiotics had a greater effect on leaf metabolites due to combination of multiple abiotic stresses. MPS, NF and SFD accumulated from roots and transported to shoots and leaves which ultimately impacts plant metabolites and, nutritional value. They subsequently impact agricultural sustainability and food safety of medicinal food plants. This investigation suggests the possible ecological risks of microplastics to medicinal food plants, especially in co-exposure with organic pollutants like antibiotics and help to reveal potential mechanisms of phytotoxicity of different antibiotics with polyethylene microplastic.